2021
DOI: 10.3389/fcimb.2021.760076
|View full text |Cite
|
Sign up to set email alerts
|

Enterochromaffin Cells: Sentinels to Gut Microbiota in Hyperalgesia?

Abstract: In recent years, increasing studies have been conducted on the mechanism of gut microbiota in neuropsychiatric diseases and non-neuropsychiatric diseases. The academic community has also recognized the existence of the microbiota-gut-brain axis. Chronic pain has always been an urgent difficulty for human beings, which often causes anxiety, depression, and other mental symptoms, seriously affecting people’s quality of life. Hyperalgesia is one of the main adverse reactions of chronic pain. The mechanism of gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 162 publications
0
15
0
Order By: Relevance
“…Nowadays, it is possible to better understand these latter findings as described in Section 2.1 for EECs and as indicated in these references [ 42 , 43 , 44 ].…”
Section: Ultrastructural Features Of Enterochromaffin Cells and Their...mentioning
confidence: 91%
See 2 more Smart Citations
“…Nowadays, it is possible to better understand these latter findings as described in Section 2.1 for EECs and as indicated in these references [ 42 , 43 , 44 ].…”
Section: Ultrastructural Features Of Enterochromaffin Cells and Their...mentioning
confidence: 91%
“…The above findings suggest a very useful role of 5-HT release from ECs, but it has been found that the proliferation of these cells and high presence of 5-HT in their vesicles are involved in visceral sensitization and hyperalgesia in irritable bowel syndrome [ 43 ]. If some receptors on duodenal mucosa ECs such as free fatty acid receptors are activated, ECs protect the small intestine mucosa regulating 5-HT biosynthesis and release, but if the stimulation of the receptors is excessive can induce the abnormal release of 5-HT.…”
Section: Heterogeneity Of Enterochromaffin Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several GI-derived peptides are also synthesized within the brain, where they act as neuromodulators and/or neurotransmitters [ 4 ]. In this context, another important player has more recently emerged, the gut microbiota, whose interaction with GI hormones seems to have a key role in the effects of diets and improving the treatment of some intestinal disorders [ 7 , 8 ]. This adds a layer of complexity in terms of characterizing the physiologic role of GI-derived peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of enterochromaffin (EC) cells and increased release of 5-hydroxytryptamine (5-HT) have been shown to contribute to the development of visceral sensitization and peripheral mechanical hyperalgesia in IBS (6)(7)(8)(9). It has been estimated that only 5% of the body's 5-HT is stored in the central nervous system and 95% is stored in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%